Long-term response of more than 9 years to regorafenib in a heavily pretreated patient with metastatic colorectal cancer. Issue 3 (15th November 2022) - Cosso, Federica; Lavacchi, Daniele; Fancelli, Sara; Caliman, Enrico; Brugia, Marco; Rossi, Gemma; Winchler, Costanza; Pillozzi, Serena; Antonuzzo, Lorenzo
Abstract : Colorectal cancer (CRC) is the third most common cancer worldwide, with approximately 1.9 million new diagnoses and 935 000 deaths annually. Overall, there is accumulating evidence that receiving all available treatments leads to a survival advantage and, although tailored treatments might be appropriate for selected patients, the one-size-fits-all approach is still widely used in chemo-refractory patients. Currently, different antiangiogenics and multitarget agents are indicated in treatment of metastatic CRC (mCRC) whereas the identification of useful predictive factors for the treatment response is lacking. Analysis of potential predictive biomarkers of efficacy of regorafenib is still ongoing but may prove to be difficult because of its nonspecific activity across a wide range of angiogenic, oncogenic, stromal, and intracellular signaling kinases. We present a case of a 57-year-old Caucasian woman diagnosed with recurrence after curative surgery for rectal adenocarcinoma stage III (ypT3N2). Despite undergoing multiple lines of standard chemotherapy, disease control could not be maintained. Consequently, regorafenib, a multikinase inhibitor with antiangiogenic proprieties, was started as a late-line treatment and a dose reduction strategy allowed a long-term response of more than 9 years with good tolerability.